Plasma Cell Cheilitis - Thami Gurvinder P; Kanwar Amrinder J; Mohan Harsh (Wolters Kluwer Medknow Publications, 1999)
A case of plasma cell cheilitis with good response to glucocorticoids, is described for its rarity and probable aetiological correlation with habit of use of nasal snuff is discussed.